Penyuluhan Keuangan Sederhana di Desa Kaduela, Kabupaten Kuningan, Jawa Barat - Devita Gantina; Nurbaeti Nurbaeti; Heny Ratnaningtyas (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2022)
This service activity aims to provide counseling, training and socialization on how to make Simple financial reports in Kaduela Village are useful for business actors in Kaduela Village so that a description of the business's financial condition can be seen. The methods used in this activity are counseling, training, and socialization. The number of participants in this activity was 27 people. The tools and materials we use are projector screens and infocus. This activity is beneficial for business actors in Kaduela Village because the preparation of good and correct financial reports will make it easier for banks to provide business loans and make it easier for investors to provide additional business funds.